Right‐sided Bochdalek hernia in an elderly patient: a case review of adult Bochdalek hernias from 1982 to 2015 in Japan. Issue 2 (10th November 2016) - Ohtsuka, Yasuhiro; Suzuki, Tiberiu H.
Abstract : Case: An 89‐year‐old woman was admitted to our hospital because of dyspnea following abdominal pain and vomiting. According to chest computed tomography findings, a diagnosis of acute respiratory failure due to right‐sided Bochdalek hernia was made. Outcome: Emergency laparotomy revealed that a bowel loop from the terminal ileum to the transverse colon had herniated into the right thoracic cavity through the foramen of Bochdalek. The herniated organs were reduced to the abdominal cavity and the foramen was repaired by direct suturing. The patient had good recovery and was discharged 78 days later. Conclusion: Bochdalek hernias in elderly patients are rare, but may be complicated by strangulation of the herniated organ. This should be taken into account by acute care physicians. To prevent this fatal complication, regardless of symptoms, surgical treatment may be essential as soon as a diagnosis of adult Bochdalek hernia is made. Abstract : Plain chest computed tomography findings on admission of an 89‐year‐old woman with right‐sided Bochdalek hernia. A, Scout view revealed bowel loops in the right thoracic cavity, which compressed the right lung to the apex of the thoracic cavity and shifted the mediastinum to the left side. B, C, Axial views at the level of Th4 (B) and Th7 (C) revealed that the bowel loops in the right thoracic cavity seemed to be the colon, which had herniated through the posterolateral portion of the right diaphragm. AA, ascending aorta; AR, arch of aorta; DA, descending aorta; PT, pulmonary trunk.